INTEGRATED REANALYSIS AND HIMAWARI-9 SATELLITE OBSERVATIONS OF WATERSPOUT FORMATION OVER THE BELIAH STRAIT (CASE STUDY: 17 JUNE 2025) - Halawa, Reinal Taruna Wahyu; Haryanto, Yosafat Donni (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2026)
This study investigates a waterspout event over the Beliah Strait, Indonesia, on 17 June 2025 between 11:30 and 13:00 WIB (04:30–06:00 UTC) using ERA5 reanalysis and Himawari-9 satellite observations. The event developed under weak synoptic forcing but was strongly influenced by mesoscale processes, including low-level wind convergence and intensifying boundary-layer vorticity. Time–height analysis revealed a deepening moist layer prior to convective development. Thermodynamic assessment from a Skew-T Log-P diagram indicated moderate atmospheric instability, with CAPE of 1204.3 J kg⁻¹, weak convective inhibition, a negative Lifted Index, and low LCL and LFC heights supporting rapid convection. Warm sea surface temperatures enhanced the low-level moisture supply over the narrow strait. Himawari-9 infrared imagery captured cloud-top cooling concurrent with peak convergence. The event was identified as a non-supercell waterspout associated with mesoscale convergence and favorable thermodynamic conditions. Keywords: Waterspout, Mesoscale Convergence, Convective Instability, Himawari-9, Beliah Strait